Nanomedicine. Magnetic nanoparticles for drug delivery and hyperthermia - New chances for cancer therapy Pharmakotherapie mittels nanomedizin. Magnetische nanopartikel für drug delivery und hyperthermie - Neue chancen für die krebsbehandlung - Alexiou, Christoph; Tietze, Rainer; Schreiber, Eveline; Lyer, Stefan (Onkologe, 2011)
The application of nanotechnology for the treatment, diagnosis, and monitoring of illnesses is summarized under the term nanomedicine. A particularly promising application is attributed to nanoparticular drug delivery systems. The goal of these new carrier systems is the selective enrichment of active substances in diseased tissue structures, an increase in bioavailability, the decrease of the active substance degradation and, above all, the reduction and/or avoidance of unwanted side effects. Apart from numerous nanosystems acting as carriers, the use of iron oxide nanoparticles has to be particularly emphasized. On the one hand, those particles are the carriers of the active substance and, on the other hand, can also be visualized with conventional imaging techniques (x-ray tomography, magnetic resonance imaging), called theranostic. In addition, they can be used for hyperthermia, another important supporting pillar of nanomedicine. Both procedures should lead to a personalized and goal-oriented therapy, which is of special medical and socioeconomic importance in view of the increasing number of cancer patients worldwide. © 2011 Springer-Verlag.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Drug delivery; Hyperthermia; Magnetic drug targeting; Nanomedicine; Nanoparticles